PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) ETNOMATEMATIKA MENGGUNAKAN KONTEKS MOTIF KAIN TENUN TIMOR - Yohanis Ndapa Deda; Hermina Disnawati (Jurnal Karya Pendidikan Matematika, 2019)
The purpose of this research was to integrate local wisdom in the Indonesia-Timor Leste border area which was realized through the development of Ethnomatematics Student worksheet (LKM) based on the community's cultural in the border area. The method used in this research is development research with formative type which is consisting of preliminary analysis and formative evaluation. Data collection techniques include documentation; walk through, tests, observations, and interviews. While the data analysis technique used is the data analysis of qualitative descriptive. Results of the research that the student worksheets of ethnomatematics using the context of woven fabric motif of Kefamenanu community who have been developed meet criteria valid, practical and effective to improve the learning achievement of ethnomatematics.